Evaluation of Allyl Isothiocyanate as a Soil Fumigant for Tomato (Lycopersicon esculentum Mill.) Production - Yu, Jialin (Plant disease, 2019)
Fusarium wilt (Fusarium oxysporum f. sp. lycopersici), root-knot nematodes (Meloidogyne spp.), and purple nutsedge (Cyperus rotundus L.) are among the most damaging soilborne pests for tomato (Lycopersicon esculentum Mill.) production in the southeastern United States. Allyl isothiocyanate (allyl ITC) was evaluated as a potential fumigant alternative for control of soilborne pathogens, nematodes, and weeds. Shank- or drip-injected allyl ITC at rates ranging from 221 to 367 kg ha-1 exhibited excellent performance, reducing the recovery of total F. oxysporum from treated soils. Shank- or drip-injected allyl ITC at 367 kg ha-1 provided equivalent control of C. rotundus compared with 1,3-dichloropropene + chloropicrin and metam potassium, respectively. Totally impermeable film (TIF) did not further reduce the recovery of F. oxysporum and various nematodes from soil treated with allyl ITC compared with virtually impermeable film (VIF). However, TIF mulch significantly improved C. rotundus control versus shank- or drip-injected allyl ITC treatments under VIF mulch. Overall, allyl ITC is an effective methyl bromide alternative against F. oxysporum, C. rotundus, and plant-parasitic nematodes Criconemella spp. and Hoplolaimus spp. in plasticulture tomato production